2004
DOI: 10.1074/jbc.m308203200
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Fibril Formation by Lens Crystallin Proteins and Its Implications for Cataract Formation

Abstract: The ␣-, ␤-, and ␥-crystallins are the major structural proteins within the eye lens and are responsible for its exceptional stability and transparency. Under mildly denaturing conditions, all three types of bovine crystallin assemble into fibrillar structures in vitro. Characterization by transmission electron microscopy, dye binding assays, and x-ray fiber diffraction shows that these species have all of the characteristics of fibrils associated with the family of amyloid diseases. Moreover, the full-length p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
190
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 177 publications
(207 citation statements)
references
References 51 publications
(44 reference statements)
17
190
0
Order By: Relevance
“…Our work has shown that each of the crystallin protein classes (α, β and γ) readily forms amyloid fibrils under mildly denaturing conditions [153]. The fibrils have all the generic structural and physical characteristics of amyloid fibrils (Fig.…”
Section: In Vitro and In Vivo Formation Of Amyloid Fibrils By Crystalmentioning
confidence: 79%
See 2 more Smart Citations
“…Our work has shown that each of the crystallin protein classes (α, β and γ) readily forms amyloid fibrils under mildly denaturing conditions [153]. The fibrils have all the generic structural and physical characteristics of amyloid fibrils (Fig.…”
Section: In Vitro and In Vivo Formation Of Amyloid Fibrils By Crystalmentioning
confidence: 79%
“…The advantage of crystallin proteins is their ready availability in significant quantity which is of particular importance if amyloid fibrils are to be used for commercial purposes. As described above, individual α-and γ-crystallin subunits readily form fibrils under mildly denaturing conditions [152,155] as do the individual α-, β-and γ-crystallin classes [153]. Our recent work has shown that semi-pure and crude mixtures of the crystallins from bovine, ovine and deer lenses formed amyloid fibrils under similar conditions employed for the preparation of crystallin fibrils, i.e.…”
Section: Crystallin Proteins As Bionanomaterialsmentioning
confidence: 96%
See 1 more Smart Citation
“…(*)The C-terminal extensions for HspB1/Hsp27, HspB2/ MKBP and HspB6/Hsp20 were identified from 1 H NMR spectroscopic studies of sHsps from other mammals, i.e. mouse, rat and rat respectively Our work with αAc and αBc has shown that they form amyloid fibrils under slightly destabilising conditions, for example, in the presence of low concentrations of denaturant and elevated temperature (Meehan et al 2004;Meehan et al 2007). The E. coli sHsp IbpA forms amyloid fibrils under physiological conditions in vitro, which is prevented by the presence of its co-chaperone IbpB (Ratajczak et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Under physiological conditions, human Bc forms large roughly spherical assemblies of 8-18 nm in diameter [7,23]. Under partially denaturing conditions and elevated temperature, Bc also assembles into amyloid fibrils as revealed by TEM and atomic force microscopy [24,25].…”
mentioning
confidence: 98%